Elaboración de indicadores de gestión del desempeño laboral para el área administrativa – financiera del hospital general provincial Luis Gabriel Dávila. De la ciudad de Tulcán - Delgado Campaña, Wilmar Alberto (2014)
Nowadays, the emphasis is on the importance of the use of indicators to measure and assess their level of performance of its employees in each of the areas of the organization, so they can get informative data to take with higher levels of responsibility according to the decisions you real environment in the process of implementing the activities. The development of indicators for administrative and financial area of the Hospital will create a culture of efficiency in carrying out the activities of the employees of the institution for promoting creativity and innovation in the employment relationship and encouraging the creation of a suitable environment for performance of the duties performed by the staff. The indicators applied to the Hospital, enable a real assessment on the implementation of the activities of staff in the administrative and financial management, achieving results that will make sound decisions, becoming a management tool to provide a secure future the scope of the objectives of the institution